Adobe Acrobat 7 : - Matthews, Marty (McGraw-Hill/Osborne, 2005)
A guide to Adobe Acrobat 7 provides information on viewing, printing, creating, and editing PDF files; using Distiller and Preflight; creating and using forms; adding multimedia and navigation; and establishing security